In-depth analysis of the photophysics of BOPAHY dyes in solution, glass and film. (October 2022) - de Jong, Flip; Verhaeghe, Davy; Veys, Koen; Huang, Jianjun; Parambil, Shandev Pookkandam; Dehaen, Wim; Escudero, Daniel; Fron, Eduard; Van der Auweraer, Mark
Abstract: BOPAHY dyes are a recently synthesized class of asymmetric highly fluorescent double boron complexed dyes. The photophysics of 5-substituted BOPAHY dyes was investigated by steady-state and time-resolved spectroscopy in liquid solution, dissolved in an organic glass and in neat spin-coated films. In the latter samples some derivatives show efficient fluorescence. The experimental results were compared with the predictions from DFT and time dependent DFT. The influence of the nature of the hetero-aromatic substituent in the 5-position on the features of the absorption and fluorescence spectra and the decay of the S1 -state is linked to the molecular morphology. The experiments show the choice of the 5-substituent is critical to avoid loss of a boron center in solution. Highlights: The photophysics of BOPAHY dyes is studied in solution, organic glass and neat film. The BOPAHY fluorophore may lose a boron center if not stabilized by a hydrogen bond. In neat film the spectra are narrower than in solution and monomer emission or emission of J-aggregates is observed.